Miocene collision-related conglomerates near Dazhuqu and Xigaze, Yarlung Tsangpo suture zone, Tibet - Chan, Angel On Kee; Aitchison, Jonathan C; Bandengzhu, Bandengzhu; Hui, Lan (Himalayan Journal of Sciences, 2008)
Himalayan Journal of Sciences Vol.2(4) Special Issue 2004 pp. 112